INTERDEPENDENSI SENI TARI DAN MUSIK IRINGANNYA - Delfi Enida (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
Interdepence of the art of dance dan its accompanying music means interrelation between the two. The performance of a dance is usually accompanied by a music, in certain occasion the performance does not use a music at all. The definition of dance usually emphasises that dance is a human expression through rhythmic and beautiful body movement and the movement is the expression of its creator to communicate directly with the audience.Body movement in a dance performance contains rhythmic elements as can be found in music, so the performance is close related to music which also contains important rhythmic elements.Music and dance has rhythm as the basis of their movement. Music can express abstract aspects of movement. It can also express the easiness and difficulty of movement. But not all music can be use to accompany a dance performance. Basically, the selection of music for a dance performance should be based  on its limitation and contribution to the performance